Balancing competitiveness and conditionality: environmental policy-making in low-regulating countries - Knill, Christoph; Tosun, Jale; Heichel, Stephan (Journal of European public policy, 2008)
This article scrutinizes the effects of economic competition on environmental standard levels in low-regulating states that intensify their economic interlinkage with high-regulating countries. In doing so, it pursues two objectives. First, we provide a detailed empirical account of the impact of economic integration on the development of environmental standards in Hungary and Mexico. Second, we offer a theoretical argument in order to explain why low-regulating countries avoid problems of remaining ‘stuck at the bottom’, although regulatory competition is effective. We argue that missing races to the bottom or stuck at the bottom effects in low-regulating countries are the result of conditionality pressures exerted by high-regulating countries. At the same time, however, low-regulating countries attempt to preserve their comparative advantage ‘through the back door’ by cultivating a lax enforcement practice.
Gesehen am 22.11.2023